Pascal’s triangle and other number triangles in Clifford analysis - Tomaz, Graça (2012)
The recent introduction of generalized Appell sequences in the framework of Clifford Analysis solved an open question about a suitable construction of power-like monogenic polynomials as generalizations of the integer powers of a complex variable. The deep connection between Appell sequences and Pascal’s triangle called also attention to other number triangles and, at the same time, to the construction of generalized Pascal matrices. Both aspects are considered in this communication.